Graphdiyne Electrocatalyst - Zhang, Jian; Feng, Xinliang (Joule, 2018)
Electrochemical oxygen reduction with high intrinsic activity was demonstrated on a few-layer sp-hybridized N doped graphdiyne nanosheet in a new Nature Chemistry article. The synthesis mechanism of doped graphdiyne and intrinsic role of sp-hybridized N in the ORR process were elucidated, advancing development of high-performance metal-free carbon electrocatalysts for oxygen reduction. Electrochemical oxygen reduction with high intrinsic activity was demonstrated on a few-layer sp-hybridized N doped graphdiyne nanosheet in a new Nature Chemistry article. The synthesis mechanism of doped graphdiyne and intrinsic role of sp-hybridized N in the ORR process were elucidated, advancing development of high-performance metal-free carbon electrocatalysts for oxygen reduction.
CRIS-Team Scopus Importer:2023-03-20